Peran Intervensi Grup Psikoterapi Suportif untuk Memperbaiki Keadaan Depresi pada Wanita Infertil di Klinik Permata Hati RSUP Dr. Sardjito Yogyakarta - Mega Dhestiana; Carla Marchira; Rukmono Siswishanto; Shofwal Widad (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: Infertility is a worldwide problem, relates to a devastating condition that can destroy couples striving to have children. It can affect both men and women, and cause psychological related distress, depression, and low self- -esteem. Most interventions using directional, complete, and integrated approach have been focused on improving the quality of life of infertile men or women. Supportive psychotherapy is an example of such interventions.Objective: The study aimed to measure the effectiveness of supportive psychotherapy intervention in treating depression among infertile women.Method: A quasi experiment design using a pre and post- -test with a control group was employed in this study. Subjects were women (n=80) with infertility cases who sought for treatment at PermataHati Clinic Dr. Sardjito hospital. during the period from April to September 2014. A modified short supportive psychotherapywas to groups of patients over the course of four sessions. The sessions were managed by trained facilitatorscomprising psychiatrist and psychologist. Personal data and Beck Depression Inventory (BDI)were then used to assess the patients depression state.Result and Discussion: Findings indicated that 59.37% of the study subjects were found to have mild depression, whereas the other 40.63% had moderate depression. A significant change in BDI scores within the treatment group was found after intervention.Conclusion:Modified short supportive psychotherapy intervention can effectivelly reduce depression on infertile women.Keywords: modified short supportive psychotherapy, depression, infertile women